2011
DOI: 10.4103/0975-7406.90112
|View full text |Cite
|
Sign up to set email alerts
|

Blue cures blue but be cautious

Abstract: Methemoglobinemia is a disorder characterized by the presence of >1% methemoglobin (metHb) in the blood. Spontaneous formation of methemoglobin is normally counteracted by protective enzyme systems, for example, nicotinamide adenine dinucleotide phosphate (NADPH) methemoglobin reductase. Methemoglobinemia is treated with supplemental oxygen and methylene blue (1–2 mg/kg) administered slow intravenously, which acts by providing an artificial electron acceptor for NADPH methemoglobin reductase. But known or susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Methylene blue should be used with caution in individuals with severe renal insufficiency and in young patients with G6PD deficiency. This group of patients can develop hemolytic anemia characterized by formation of Heinz bodies without any reduction in MetHb levels [ 14 , 20 , 23 ]. Alternative therapies include exchange transfusion, hyperbaric oxygen, and ascorbic acid [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methylene blue should be used with caution in individuals with severe renal insufficiency and in young patients with G6PD deficiency. This group of patients can develop hemolytic anemia characterized by formation of Heinz bodies without any reduction in MetHb levels [ 14 , 20 , 23 ]. Alternative therapies include exchange transfusion, hyperbaric oxygen, and ascorbic acid [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…G6PD enzyme protects the blood cells against oxidative damage by maintaining the level of the NADPH. The NADPH in turn maintains the supply of reduced glutathione in the cells that is used to neutralize reactive oxygen species (Sikka et al, 2011). Previous study on G6PD variants found six German Ancestral G6PD variants (Roman and Swindells, 2011) of which, three particular variants (Vancouver, Aachen and Wayne) were found to locate within the active site region (Figure 1).…”
Section: Introductionmentioning
confidence: 89%
“…Another compound which is potentially connected with 17β‐HSD10 modulation is methylene blue (MB, methylthionium chloride, 19, Figure 9) (Zakaria, Hamdi, & Abdel‐Kader, 2016). MB is an FDA approved drug for methemoglobinemia therapy (Sikka, Kapoor, Saxena, Bindra, & Jain, 2011), but recently came into interest as a possible therapy for Alzheimer´s disease. Methylene blue is reported to enhance cell viability, reduce Aβ oligomerization, and both 17β‐HSD10 function and protein expression level in LPS (lipopolysaccharide) mouse model (Zakaria et al., 2016).…”
Section: Inhibition Of 17β‐hsd10‐aβ Interaction or Enzymatic Activitymentioning
confidence: 99%